2018
DOI: 10.1155/2018/2426138
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism Plays a Key Role during Macrophage Activation

Abstract: Monocyte and macrophage diversity is evidenced by the modulation of cell surface markers and differential production of soluble mediators. These immune cells play key roles in controlling tissue homeostasis, infections, and excessive inflammation. Macrophages remove dead cells in a process named efferocytosis, contributing to the healthy tissue maintenance. Recently, it became clear that the main macrophage functions are under metabolic control. Modulation of glucose, fatty acid, and amino acid metabolism is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 83 publications
(110 reference statements)
1
55
0
Order By: Relevance
“…In summary, active manipulation of amino acid metabolism is a strategy widely used by different classes of pathogens to modulate and suppress host innate immune responses. In addition to the amino acids described here, others, such as glutamine and glycine, also play important roles in immune responses [95,96]. Whether pathogens target their metabolism too, to modulate immune responses is still on open question.…”
Section: Asparaginementioning
confidence: 94%
“…In summary, active manipulation of amino acid metabolism is a strategy widely used by different classes of pathogens to modulate and suppress host innate immune responses. In addition to the amino acids described here, others, such as glutamine and glycine, also play important roles in immune responses [95,96]. Whether pathogens target their metabolism too, to modulate immune responses is still on open question.…”
Section: Asparaginementioning
confidence: 94%
“…Regulation of macrophage metabolic activity in the context of efferocytosis (Figure 2) is of major importance for the outcome of inflammation resolution and tissue repair (99). Following engulfment, macrophages degrade the apoptotic material through phagolysosomal activity (100,101), resulting in substantial metabolic load and influence on macrophage metabolism (17).…”
Section: Metabolic Modulation Of Macrophage Function In the Context Omentioning
confidence: 99%
“…Lipids deriving from the apoptotic cargo are abundant postengulfment digestion products (17); lipid metabolism induces activation of the nuclear receptors peroxisome proliferatoractivated receptor (PPAR) gamma and delta, LXR alpha and beta and retinoid × receptor (RXR) alpha and beta (107) in macrophages (Figure 2). Activation of these transcription factors promotes upregulation of phagocytic receptors and bridging molecules and the resolving macrophage phenotype.…”
Section: Metabolic Modulation Of Macrophage Function In the Context Omentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal bacteria and fungi can alter the immune system in determining the response to radiation. It was shown that during macrophage polarization, the metabolic situation of the cell would be changed (131). Radiotherapy response or resistance is highly dependent on tumor microenvironment (TME).…”
Section: Microbe-chemo Therapiesmentioning
confidence: 99%